Bioprospecção de fungos produtores de biosurfactantes e desenvolvimento de bioprocessos aplicados à micorremediação de solos contaminados com hidrocarbonetos - Silva, André Felipe da (Universidade Federal de Santa Catarina, 2023)
Environmental contamination by hydrocarbons and toxic metals is a global problem that harms all living beings. Fungi are biological resources in bioprocesses development that may be used in environmental remediation due to their ability to interact and/or produce metabolites that favor interacting with the contaminant, e.g., biosurfactants. This work aimed to explore fungal bioprocesses and bioproducts for environmental remediation and industrial applications and begin biosurfactant production development by filamentous fungi. In this context, technicalscientific advances in developing fungal bioproducts for remediation of petroleum hydrocarbons and toxic metals were reviewed, as well as the main classes of biosurfactants and the bioprocessing of fungal biosurfactants from the isolation of strains to their formulation into commercial products. A culture collection of 58 fungi isolated from hydrocarbon-contaminated soils (REMA/UFSC) was created. Strains were identified as Fusarium (n= 40), Penicillium (n= 8), Paecilomyces (n= 4), Scolecobasidium (n= 1), Scopulariopsis (n= 1) and Ilyonectria (n= 1), using morphological characteristics and/or ITS region sequencing. These isolates and other strains from contaminated soils (n = 7), Antarctic soils (n = 46), and mangrove plant endophytes (n = 7) were bioprospecting for biosurfactant production by drop collapse test, emulsification index, and tensiometry. These tests revealed the potential of Aspergillus sp. SC21P3, Fusarium sp. AF99PD, Thelebolus sp. SC29P3, Paecilomyces sp. AF45D and Ilyonectria sp. AF25D for drop collapse (>4 mm), and except the last two for tensiometry. The use of yeast extract (Medium X and Y) or NaNO3 (Medium N) at concentrations of 0.5 g•L -1 (Medium X) and 5 g•L - 1 (Medium Y and N) together with glucose (20 g•L -1 ) and soybean oil (0.5%) influenced the surface activity of biosurfactants, as well as the kinetic profile of this production. In 168h, the N medium composition promoted the highest surface tension reduction using inoculum ...